Lactiplantibacillus plantarum for the Preparation of Fermented Low-Bitter Enzymatic Skim Milk with Antioxidant Ability - Yi Jiang; Longfei Zhang; Yushi Jin; Haiyan Xu; Yating Liang; Zihan Xia; Chenchen Zhang; Chengran Guan; Hengxian Qu; Yunchao Wa; Wenqiong Wang; Yujun Huang; et al. (Foods)
A high degree of hydrolysis can reduce the allergenicity of milk, while lactic acid bacteria (LAB) fermentation can further enhance the antioxidant ability of enzymatic milk. LAB with a strong antioxidant ability was screened, and the effects of LAB on the bitterness, taste and flavor of enzymatic skim milk (ESM) with a high degree of hydrolysis were investigated in this paper, in addition to the response surface methodology optimized the conditions of the LAB fermentation of ESM. The results indicate that the skim milk hydrolyzed by Protamex has a higher degree of hydrolysis and lower bitterness. The scavenging rate of 2,2-Diphenyl-1-picrylhydrazyl (DPPH) free radical, the inhibition rate of hydroxyl radical (·OH) and the superoxide dismutase (SOD) activity of Lactiplantibacillus plantarum 16 and Lactococcus lactis subsp. lactis m16 are significantly higher than those of other strains (p < 0.05), while the improvement effect of L. plantarum 16 on the bitterness and flavor of ESM is better than that of L. lactis subsp. lactis m16. The fermented ESM has a strong antioxidant ability and low bitterness when the inoculum quantity of L. plantarum 16 is 5%, fermentation at 37 °C for 18 h and the pH of the ESM is 6.5, for which the DPPH free radical scavenging rate is 61.32%, the ·OH inhibition rate is 83.35%, the SOD activity rate is 14.58 and the sensory evaluation is 4.25. The contents of amino acids related to bitterness and antioxidants were reduced and increased, respectively. The ESM fermented by L. plantarum 16 has a good flavor, antioxidant ability and low bitterness.